A Telephone Call to Decrease Patient Anxiety Before Urodynamic Testing: A Randomized Controlled Trial. Issue 5 (September 2019) - Warda, Hussein; Hacker, Michele R.; Haviland, Miriam J.; Hota, Lekha S.
Abstract : Objective: The aim of this study was to determine if a telephone call before undergoing urodynamic study (UDS) would decrease test-related anxiety compared with standard care. Methods: We performed a randomized controlled trial at a single practice from April 2016 to June 2017. Patients at least 18 years old with lower urinary tract dysfunction and undergoing UDS for the first time were eligible. All participants received standard counseling; participants randomized to the intervention group also received a telephone call before their UDS appointment to answer any questions regarding their upcoming test. All participants completed surveys before and after testing to assess anxiety, preparedness, and satisfaction. The primary outcome was anxiety level immediately before UDS. Secondary outcomes included self-reported patient preparedness, pain, and satisfaction with counseling. Data were compared using χ 2, Fisher exact, and Wilcoxon rank sum tests. Results: One hundred two participants were included in this as-treated analysis: 52 in the intervention group and 50 in the standard care group. The 2 groups were similar in age, ethnicity, and the proportion seeking additional information before testing. There were no statistically significant differences between groups with respect to overall anxiety, anxiety regarding specific elements of the test, or anticipated pain (all P ≥ 0.19). Participant satisfaction with pre-UDS counseling was significantly higher in the intervention group (80.8%) compared with the standard care group (54.0%; P = 0.002). Conclusions: Our study showed that a telephone call before undergoing UDS did not decrease anxiety compared with standard care; however, the telephone call was associated with higher satisfaction with pre-UDS counseling.